Proposed Knowledge Management System to Improve Productivity in Strategy and Analytics PT. XL Axiata Tbk - Dimas Natajiwa (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
This study tackles important productivity issues in PT. XL Axiata Tbk's Strategy and Analytics division, such as an excessive dependence on individual workers, a dearth of centralized documentation, protracted onboarding, and uneven deliverable quality. Delays, poor First Time Right (FTR) rates, and decreased operational agility have all been caused by these problems. Interviews, observations, and document analysis were all combined in a qualitative manner. Four major gaps were found by thematic analysis: a lack of standardized and centralized documentation, a high reliance on key PIC, a lack of knowledge evaluation, and limited knowledge sharing practices. The study uses a Knowledge Management (KM) Strategy based on People, Process, and Technology in conjunction with the SECI Model (Socialization, Externalization, Combination, Internalization) to address these problems. By integrating KM practices into everyday operations, this integration offers an organized method for gathering, disseminating, and applying organizational knowledge. Creating KM governance, designating KM Champions, standardizing documentation templates, incorporating a centralized DataHub repository, and putting peer review procedures in place are important solutions. The Foundational, Implementation, and Evaluation phases of a phased knowledge management roadmap were created to direct execution and gauge results using KPIs like higher FTR rates, shorter onboarding times, repository usage, and employee satisfaction. The study comes to the conclusion that successful knowledge management requires a thorough organizational transformation effort rather than just a technology initiative. Through organizational, procedural, and technological interventions, the division can enhance productivity, improve the quality of deliverables, and cultivate a culture of sustainable knowledge-sharing that supports XL Axiata's strategic goals in the telecom industry